A Novel Rat Model of Blast-Induced Traumatic Brain Injury Simulating Different Damage Degree: Implications for Morphological, Neurological, and Biomarker Changes - Liu, Mengdong; Zhang, Chi; Liu, Wenbo; Luo, Peng; Zhang, Lei; Wang, Yuan; Wang, Zhanjiang; Fei, Zhou (Frontiers in Cellular Neuroscience, 2015)
In current military conflicts and civilian terrorism, blast-induced traumatic brain injury (bTBI) is the primary cause of neurotrauma. However, the effects and mechanisms of bTBI are poorly understood. Although previous researchers have made significant contributions to establishing animal models for the simulation of bTBI, the precision and controllability of blast-induced injury in animal models must be improved. Therefore, we established a novel rat model to simulate blast-wave injury to the brain. To simulate different extents of bTBI injury, the animals were divided into moderate and severe injury groups. The miniature spherical explosives (PETN) used in each group were of different sizes (2.5 mm diameter in the moderate injury group and 3.0 mm diameter in the severe injury group). A specially designed apparatus was able to precisely adjust the positions of the miniature explosives and create eight rats with bTBI simultaneously, using a single electric detonator. Neurological functions, gross pathologies, histopathological changes and the expression levels of various biomarkers were examined after the explosion. Compared with the moderate injury group, there were significantly more neurological dysfunctions, cortical contusions, intraparenchymal hemorrhages, cortical expression of S-100β, MBP, NSE, IL-8, IL-10, iNOS and HIF-1α in the severe injury group. These results demonstrate that we have created a reliable and reproducible bTBI model in rats. This model will be helpful for studying the mechanisms of bTBI and developing strategies for clinical bTBI treatment.